A million-channel reformer on a fingertip: Moving down the scale in hydrogen production - Lopez, Eduardo (2010)
The present contribution reports the design, manufacture and experimental proof of concept of an ethanol micro-reformer for portable-fuel cell feeding. Through photo-assisted electrochemical etching, a silicon micromonolithic substrate with perfectly parallel cylindrical channels of 3.3 μm diameter was achieved (density of channels of ca. 4 × 104 channels mm-2). The channel walls were coated with a cobalt-based catalyst. The resultant functionalized micromonoliths were implemented in a stainless steel microreactor including feed evaporation facilities and electrical heating. The unit was successfully tested for ethanol steam reforming under non-diluted feed conditions at 773 K, achieving high hydrogen specific production rates, high ethanol conversions (>80%) and adequate selectivity profiles, with H2:CO2 molar ratios of ∼3 and low CO outlet concentrations. A performance comparison was performed with two other reforming substrates with the same catalyst formulation, namely, a conventional cordierite monolith and a conventional stainless steel microreactor. Results show for the Si-micromonolithic reactor a remarkable improvement of the specific hydrogen production rate (per unit reactor volume and feed flowrate), operating at considerably reduced residence times, due to the increase in contact area per unit volume. © 2010 Professor T. Nejat Veziroglu.